The placental transfer of IgG subclasses in human pregnancy. - Pitcher-Wilmott, R W (1980)
Total IgG concentrations and the concentrations of the four subclasses of IgG were estimated in thirty-four pairs of maternal and foetal sera from pregnancies of various gestations ranging from 28 to 42 weeks using the method of radial immunodiffusion. It was found that: (1) all subclasses of IgG cross the human placenta freely, (2) foetal levels of IgG and each subclass of IgG exceed maternal levels in full-term pregnancies and (3) there was a close linear relationship between gestational age and the placental transfer of IgG and each of its subclasses.